Observations of Waves and Structures by Frequency–Wavenumber Spectrum in Solar Wind Turbulence - L.-L. Zhao; G. P. Zank; M. Nakanotani; L. Adhikari (The Astrophysical Journal, 2023)
A well-known shortcoming of single-spacecraft spectral analysis is that only the 1D wavenumber spectrum can be observed, assuming the characteristic wave propagation speed is much smaller than the solar wind flow speed. This limitation has motivated an extended debate about whether fluctuations observed in the solar wind are waves or structures. Multispacecraft analysis techniques can be used to calculate the wavevector independent of the observed frequency, thus allowing one to study the frequency–wavenumber spectrum of turbulence directly. The dispersion relation for waves can be identified, which distinguishes them from nonpropagating structures. We use magnetic field data from the four Magnetospheric Multiscale (MMS) spacecraft to measure the frequency–wavenumber spectrum of solar wind turbulence based on the k -filtering and phase differencing techniques. Both techniques have been used successfully in the past for the Earth’s magnetosphere, although applications to solar wind turbulence have been limited. We conclude that the solar wind turbulence intervals observed by MMS show features of nonpropagating structures that are associated with frequencies close to zero in the plasma rest frame. However, there is no clear evidence of propagating Alfvén waves that have a nonzero rest-frame frequency. The lack of waves may be due to instrument noise and spacecraft separation. Our results support the idea of turbulence dominated by quasi-2D structures.